Schools of public health in low and middle-income countries: an imperative investment for improving the health of populations?. (December 2016) - Rabbani, Fauziah; Shipton, Leah; White, Franklin; Nuwayhid, Iman; London, Leslie; Ghaffar, Abdul; Ha, Bui; Tomson, Göran; Rimal, Rajiv; Islam, Anwar; Takian, Amirhossein; Wong, Samuel; et al.
Abstract Background Public health has multicultural origins. By the close of the nineteenth century, Schools of Public Health (SPHs) began to emerge in western countries in response to major contemporary public health challenges. The Flexner Report (1910) emphasized the centrality of preventive medicine, sanitation, and public health measures in health professional education. The Alma Ata Declaration on Primary Health Care (PHC) in 1978 was a critical milestone, especially for low and middle-income countries (LMICs), conceptualizing a close working relationship between PHC and public health measures. The Commission on Social Determinants of Health (2005–2008) strengthened the case for SPHs in LMICs as key stakeholders in efforts to reduce global health inequities. This scoping review groups text into public health challenges faced by LMICs and the role of SPHs in addressing these challenges. Main text The challenges faced by LMICs include rapid urbanization, environmental degradation, unfair terms of global trade, limited capacity for equitable growth, mass displacements associated with conflicts and natural disasters, and universal health coverage. Poor governance and externally imposed donor policies and agendas, further strain the fragile health systems of LMICs faced with epidemiological transition. Moreover barriers to education and research imposed by limited resources, political and economic instability, and unbalanced partnerships additionally aggravate the crisis. To address these contextual challenges effectively, SPHs are offering broad based health professional education, conducting multidisciplinary population based research and fostering collaborative partnerships. SPHs are also looked upon as the key drivers to achieve sustainable development goals (SDGs). Conclusion SPHs in LMICs can contribute to overcoming several public health challenges being faced by LMICs, including achieving SDGs. Most importantly they can develop cadres of competent and well-motivated public health professionals: educators, practitioners and researchers who ask questions that address fundamental health determinants, seek solutions as agents of change within their mandates, provide specific services and serve as advocates for multilevel partnerships. Funding support, human resources, and agency are unfortunately often limited or curtailed in LMICs, and this requires constructive collaboration between LMICs and counterpart institutions from high income countries.